Model of Empowering Muslim Minority Communities Through Productive Zakat: A Case Study of Baznas North Sumatra - Farhan Khairi Muzanni Tarigan; Juliana Nasution (Journal of Islamic Economics Perspectives, 2026)
Productive zakat has increasingly been positioned as a strategic instrument for sustainable socio-economic transformation, particularly within vulnerable and marginalized communities. Situated within the discourse of environmental sustainability and moral Islamic economics, this study examines the empowerment model of Muslim minority communities implemented by BAZNAS North Sumatra. Using a qualitative document-based approach, the research analyzes institutional reports, regulatory frameworks, and scholarly literature to explore how productive zakat mechanisms contribute to long-term welfare improvement. The findings indicate that productive zakat functions not merely as a redistributive financial tool but as a moral-economic intervention fostering economic resilience, social cohesion, and sustainable livelihood strategies. The study highlights that empowerment outcomes are shaped by the systemic integration of economic, educational, social, and spiritual dimensions, reinforcing ethical agency and value-driven development. By linking Islamic social finance with sustainability-oriented frameworks, this research contributes to emerging debates on moral economic governance and sustainable community development across diverse Muslim socio-economic contexts.